The Influence of Work Discipline and Communication on Employee Performance: On One of The Marketplaces in The Form of Websites and Applications in The Agribusiness Sector - Purwadayana, Yulianthy; Riadi, Farid; Zulfikar, Vicky Achmad; Rinawati, Nenny (Center of Research, STIE Pasundan, Bandung, Indonesia., 2024)
This study aims to investigate and analyze the impact of work discipline and communication on employee performance in the agricultural industry, specifically in the context of websites and applications used in marketplaces. The research methodology employed consists of descriptive and verification techniques. The researchers employed a questionnaire as the data-collecting method, which was sent to 43 individuals. The instrument underwent rigorous testing before its deployment to ensure its validity and reliability. The statistical technique employed was path analysis, conducted using SPSS version 25 software. According to the research findings, employees' motivation and work discipline in a marketplace operating as a website and application in the agribusiness sector were judged to be satisfactory. Work discipline and communication impact on employee performance account for 83.3%, while the remaining 16.6% is attributed to other variables. The results indicate that the combination of work discipline and communication substantially impacts employee performance in the agricultural industry, specifically in the marketplace of websites and applications.